Microcephaly, Dysmorphic Features, Corneal Dystrophy, Hairy Nipples, Underdeveloped Labioscrotal Folds, and Small Cerebellum in Four Patients - Kayserili, Hulya; Altunoglu, Umut; Yesil, GÖZDE; YEŞİL, GÖZDE; Rosti, Rasim Ozgur (My University, 2016)
Pontocerebellar hypoplasia (PCH) can occur as an isolated entity or part of a syndrome. PCH has been reported with facial dysmorphism, ocular anomalies, and genital anomalies, but the co-occurrence of all four has not been previously described. We report on four patients, born to two consanguineous families that are not related to one another, with distinctive facial features (short forehead, laterally extended, medially flared eyebrows), corneal dystrophy, underdevelopment of labioscrotal folds, and nonprogressive PCH. In addition, the patients show hair extruding from the lactiferous ducts, which to our knowledge has not been described before. The parental consanguinity, affected siblings of both genders, and absent manifestations in parents, indicate an autosomal recessive pattern of inheritance as most likely. (C) 2016 Wiley Periodicals, Inc.